THE INTERRELATION BETWEEN LANGUAGE AND CULTURE IN INTEGRATED ENGLISH TEACHING COURSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the close interrelation between language and culture within the framework of integrated English teaching courses. It examines how cultural awareness enhances language acquisition and communication skills. The study emphasizes the importance of incorporating cultural content in teaching English, including traditions, social norms, and values, to develop learners’ intercultural competence. Strategies for integrating culture in language lessons, such as authentic materials, multimedia resources, and project-based learning, are discussed. The article also highlights challenges and recommendations for effective implementation in classroom settings.